Long‐term edaravone efficacy in amyotrophic lateral sclerosis: Post‐hoc analyses of Study 19 (MCI186‐19). Issue 2 (11th November 2019) - Shefner, Jeremy; Heiman‐Patterson, Terry; Pioro, Erik P.; Wiedau‐Pazos, Martina; Liu, Shawn; Zhang, Jeffrey; Agnese, Wendy; Apple, Stephen
Abstract: Background: In a Phase 3 study, amyotrophic lateral sclerosis (ALS) patients experienced significantly less physical functional decline with 24‐week edaravone vs placebo, followed by open‐label treatment for an additional 24 weeks. Methods: Outcome (the change in ALS Functional Rating Scale–Revised, ALSFRS‐R, from baseline) was projected for placebo patients through 48 weeks and compared with 48‐week edaravone or 24‐week edaravone after switching from placebo. Results: A total of 123 patients received open‐label treatment (65 edaravone‐edaravone; 58 placebo‐edaravone). The projected ALSFRS‐R decline for placebo from baseline through week 48 was greater than for 48‐week edaravone ( P  < .0001). For patients switching from placebo to edaravone, ALSFRS‐R slope approached that of continued edaravone for 48 weeks. ALSFRS‐R decline did not differ between actual and projected edaravone through week 48. Conclusions: Compared with placebo, these analyses suggest that edaravone is beneficial in ALS patients even after 6 mo of receiving placebo, and efficacy is maintained for up to 1 year. Abstract : See editorial on pages 129–130 in this issue .